PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 142 PEKANBARU - Yuliani, Anita; Marhadi, Hendri; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. This research is motivated by the low value of math studies of class II elementary school 142 Pekanbaru, because the teacher relate the problems in daily life, the students don’t understand master the material and students can’t focus on learning. Based on these problems, it is necessary given way to solve the problem include applying model based learning problems. subjects in this research were 33 students of class II of 142 elementary school Pekanbaru. This research was conducted in two cycles, by doing the daily test of the end of each cycle. The result of first cycle show that the teacher’s activity was good and student activity was good too but must increase in activ student and teamwork. In second cycle, the teacher and student activity is better and the student more active than before. The result of this research shows that the implementation of model based learning problems can improve learning outcomes with base score of 62,42 after restating daily 1 increased 1,82% to 64,24 then increased again 15,45% to 79,69. based learning problems model can increase math studies, completeness math learning outcomes in first cycle is 45,46%, and increased to 90,99% in second cycle. It means that the implementation of model based learning problems can increase math studies of class II of 142 elementary school Pekanbaru.Keywords : Based Learning Problems, Mathematics Learning Outcomes.